2006
DOI: 10.1002/mde.1251
|View full text |Cite
|
Sign up to set email alerts
|

Sales by multi-product retailers

Abstract: This paper examines the rationale underlying periodic price promotions, or sales, for perishable food products by supermarket retailers. Whereas previous studies explain sales in a single-product context as arising from informational, storage cost, or demand heterogeneity, this study focuses on the central role of retailers as multi-product sellers of complementary goods. By offering a larger number of discounted products within a particular category, retailers are able to attract a sufficient number of custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 75 publications
(68 reference statements)
1
12
1
1
Order By: Relevance
“…The empirical evidence provided in Richards (2006) however contradicts this result. Breadth and depth of price promotions are found to be complementary marketing tools in four major supermarket chains in the Los Angeles market.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…The empirical evidence provided in Richards (2006) however contradicts this result. Breadth and depth of price promotions are found to be complementary marketing tools in four major supermarket chains in the Los Angeles market.…”
contrasting
confidence: 62%
“…. ; n 1 ) to maximize total store profits (this equation corresponds to Equation (1) on p. 265 in Richards, 2006) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is impossible to review all contributions here, we will mention a few analyses which provide rationales for promotions that are particularly pertinent to our model. Richards () showed that multiproduct retailers could use sales to contend customers; similarly Volpe () discussed promotion competition across stores as an alternative to price wars. Xia and Sexton () suggested that multiproduct retailers can rotate the products on promotional sales to price discriminate among heterogeneous consumers.…”
Section: Empirical Features Of Agricultural and Food Pricesmentioning
confidence: 99%
“…Finally, small supermarkets are found to have a significantly smaller rank variability as opposed to the largest supermarkets in the sample (the left-out category). This gives some support to Richards (2004), who shows that HILO and EDLP stores can coexist in the same competitive environment as well as Buckle and Carlson (2000), who argue that larger firms have greater benefits from price adjustments and will thus adjust prices more quickly to cost and demand changes. On the other hand, our results contradict Haruvy and Erev (2001) who suggest that a strategy of frequent price adjustment (HILO strategy) is particularly attractive for small (high-cost) stores.…”
Section: Store Differences In Rank Stabilitymentioning
confidence: 62%